PENGARUH STRUKTUR MODAL, KEPUTUSAN INVESTASI, PROFITABILITAS SEBAGAI VARIABEL MEDIASI TERHADAP NILAI PERUSAHAAN : STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wijayanti, Sekar Arum; Setiawati, Erma (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the influence of capital structure, investment decisions, and profitability as mediating variables on company value. This study uses a quantitative method. The population in this study is all food and beverage adapter companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sample of this study uses purposive sampling. The data analysis method in this study uses multiple linear regression analysis. The data sources of this research are using primary data and secondary data. The results of the study show that the variables of capital structure and profitability have an effect on the value of the company, while the variables of investment decisions have no effect on the value of the company. Capital structure variables and investment decisions affect profitability. The profitability variable cannot mediate the influence of capital structure on the value of the company, and profitability cannot mediate the influence of investment decisions on the value of the company